Association of high sensitive C-reactive protein with coronary heart disease: a Mendelian randomization study - Qian Zhuang; Chong Shen; Yanchun Chen; Xianghai Zhao; Pengfei Wei; Junxiang Sun; Yanni Ji; Xiaotian Chen; Song Yang (BMC, 2019)
Abstract Objectives Whether high sensitivity C-reactive protein (hs-CRP) has a causal effect on coronary heart disease (CHD) is unclear. This study investigated the causal effect of hs-CRP on CHD risk using Mendelian Randomization (MR) analysis. Methods A total of 3802 subjects were recruited in the follow-up study. Linear regression model was used to evaluate the relationship between CRP polymorphisms and hs-CRP. Survival receiver operator characteristic curve method was used to explore the cut-off of hs-CRP on CHD incidence. Cox regression model was applied to detect the association of hs-CRP with CHD by calculating the hazard ratio (HR) and 95% confidence interval (CI). Rs1205 and rs876537 in CRP were selected as instrumental variables in MR analysis. Results During a median follow-up time of 5.01 years, 98 CHD incidence was identified (47.03/104 person-years). Hs-CRP was significantly increased among rs1205 and rs876537 genotypes with r values of 0.064 and 0.066, respectively. Hs-CRP 1.08 mg/L was identified as the cut-off value with a maximum value of sensitivity and specificity on prediction of CHD. Participants with ≥1.08 mg/L of hs-CRP has a higher risk of CHD incidence than that of participants with < 1.08 mg/L, the adjusted HR (95% CI) was 1.69 (1.11-2.60) with a P value of 0.016. No significant casual association was observed between hs-CRP and CHD with a P value of 0.777. Conclusions The association between hs-CRP and CHD is unlikely to be causal, hs-CRP might be a predictor for incidence of CHD in general population.